Polymorphisms of the matrix metalloproteinase 9 gene are associated with duodenal ulcer in a Caucasian population of Central Russia - Oksana Minyaylo; Irina Ponomarenko; Evgeny Reshetnikov; Volodymyr Dvornyk; Mikhail Churnosov (Journal of King Saud University: Science, 2022)
Objectives: The aim of this study was to analyze functionally significant polymorphisms of matrix metalloproteinases genes (MMP-1, -2, -3, -8, -9) for their association with duodenal ulcer (DU) in the Caucasian population from Central Russia. Methods: The study sample included 364 DU patients (208 had H. pylori and 156 were uninfected) and 347 controls (H. pylori-negative). Ten polymorphisms of the MMP-1, -2, -3, -8, -9 genes were examined for association with DU by the logistic regression analysis (used the three main genetic models). The polymorphisms of the MMP-9 gene associated with DU and 59 proxy variants (r2 ≥ 0.80) were studied in silico for their functionality. Results: Allele G of rs17576 and haplotype GG [rs17576-rs3787268] of the MMP-9 gene may increase risk for DU (adjOR = 1.46–2.09, pperm ≤ 0.006 and adjOR = 1.60, pperm = 0.016 respectively). Five SNPs of the MMP-9 gene may increase risk for H. pylori-positive DU: alleles T of rs3918242 (adjOR = 1.95, pperm = 0.007), G of rs17576 (adjOR = 1.68–2.81, pperm ≤ 0.002), and A of rs17577 (adjOR = 1.96, pperm = 0.008), haplotypes GG [rs17576-rs3787268] (adjOR = 1.95, pperm = 0.006) and GGC [rs17576-rs3787268-rs2250889] (adjOR = 1.96, pperm = 0.006). These loci and 59 proxy SNPs may have functionally significant epigenetic effects, amino acid replacements in the MMP9, and correlate with the expression and alternative splicing of 17 and 6 genes respectively. Conclusions: Polymorphisms rs17576 and rs3787268 of the MMP-9 were associated with DU and five MMP-9 gene SNPs were associated with H. pylori-related DU in Caucasians of Central Russia.